Penerapan Model Pembelajaran Example non Example Untuk Meningkatkan Hasil Belajar Matematika Penjumlahan Pada Siswa Kelas II Sekolah Dasar (SD) Muhammadiyah I Gotalamo Kecamatan Morotai Selatan - Nurhani Mahmud; Astuti Muksin (Peneliti.net, 2021)
This study aims to determine the learning outcomes of compound addition mathematics through the example non example learning model for second grade students of SD Muhammadiyah I Gothalamo, South Morotai District. This type of research is Classroom Action Research (CAR) with 20 students as research subjects. This action research was conducted in two cycles consisting of the stages of planning, implementation, observation and reflection. Techniques for collecting data through observation and tests and data were analyzed in quantitative form. The results of this study indicate that the application of the example non example learning model can improve student and teacher learning outcomes in the teaching and learning process. Student learning outcomes from Cycle I score of 30% (6 students) who completed increased and in Cycle II there was an increase in score of 90% (18 students) who completed. Classically, learning outcomes have reached the KKM 70 standard.